Implementation of Digital Technology-Based Learning Model to Enhance Student Engagement and Motivation in Economics Subject Learning at High School - Hariyono, Hariyono (STAI Miftahul Ula Nganjuk, 2023)
This article discusses the scientific ideas behind the development of a technology-based digital learning model to enhance economics education in high schools (SMA) in Indonesia. Fundamental concepts such as the utilization of digital technology, project-based and collaborative learning models, positive feedback, and inclusive learning form the primary foundation. The article analyzes how these concepts can be integrated into an effective and efficient learning model. Strategies include the development of interactive digital platforms, learning models integrated with the real world, timely feedback provision, and specialized support for students with special needs. The article outlines implementation steps, potential challenges, and positive impacts such as increased motivation, effectiveness, and student engagement. In a broader educational context, these ideas can be adapted for various levels and developing countries. In conclusion, the article illustrates efforts to enhance learning through innovative models that integrate digital technology and effective learning principles.